Building public trust through an anti-bullying program in Islamic boarding schools: synergy of the four matra of education - Baharun, Hasan; Halimatus Sa’diyah (UIN Salatiga, 2025)
This study aims to explore how an Islamic boarding school-based anti-bullying program can build public trust by utilizing religious values and local wisdom. Bullying in educational settings has eroded public trust, prompting the need for effective prevention programs. The research integrates four key educational dimensions: students, parents, teachers/administrators, and the government, to address this issue. Using a qualitative case study approach, this study examines the role of Islamic boarding schools in fostering mutual respect and creating a safe learning environment. The program involves peer educators and parents as key observers, helping to detect bullying early and provide social support. Findings show that collaboration among these parties enhances bullying prevention, promotes a sense of security, and rebuilds public trust in Islamic boarding schools. The study contributes to developing a model for bullying prevention in Islamic educational settings, emphasizing the importance of cooperation between schools, families, and the government. Public trust is built by demonstrating a commitment to student welfare, grounded in the synergy of the four pillars of education.